Is it a myth? Market power among intermediaries in agri-food value chains - de Brauw, Alan; Maruyama, Eduardo; Wagner, Julia (International Food Policy Research Institute, 2024)
A common narrative about agri-food value chains (AVCs) in low- and middle-income countries (LMICs) is that smallholders are paid substantially less for their agricultural products relative to the prices consumers pay for them. Some of that difference can be attributed to market channels—even in competitive and efficient agricultural markets, there are costs involved as agricultural products move from producers to consumers, including expenses for transportation, collection and aggregation, grading, processing, distribution, packaging, and retailing.